Studies on Agronomic Bio-fortification with Micronutrients in Onion (Allium cepa L.) Seed Crop - Dogra, Rupali; Thakur, Ashok K.; Sharma, Uday (International Journal of Economic Plants, 2019)
In the present investigations, carried out at experimental farm and laboratory of Department of Seed Science and Technology, Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, HP during 2015-2017, seed crop of onion cv. Palam Lohit was sprayed with zinc, boron, molybdenum and their combinations. Foliar application of micronutrients was given as zinc sulphate, boric acid and sodium molybdate at a concentration of 5%, 1% and 0.05%, respectively, at 3 stages i.e. vegetative stage, prior to flowering and at seed set stage. The sprays of zinc @ 5% and boron @ 1% showed maximum values with respect to number of leaves plant-1 (12.67), leaf length (49.53 cm), plant height at final harvest (54.60 cm), number of umbel plant-1 (7.60), number of flower umbel-1 (465), number of seeds umbel-1 (386.67), seed yield (222.67 g plot-1 of 3.24 m2 i.e. 618.52 kg ha-1), 1000 seed weight (3.97 g) and minimum for ovule to seed ratio (7.21) and days to bolting (113.43). The present studies revealed that onion seed crop sprayed with zinc @ 5% and boron @ 1% at vegetative stage, prior to flowering and at seed set stage significantly enhanced plant growth, yield contributing characters and seed yield.